PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA PADA MATERI MATRIKS DI KELAS XI MIPA SMA NEGERI 1 MOTOLING - Jodie A. Jacob; Santje M. Salajang; Marvel G. Maukar (CV. ADIBA AISHA AMIRA, 2022)
The current mathematical learning model demands a standardized process that can promote various learning abilities, one of which is the ability to understand mathematical concepts. After a survey was conducted in one of the schools in the Motoling sub-district, namely SMA Negeri 1 Motoling, it turned out that a problem was found during the covid-19 pandemic, namely the lack of understanding of students' mathematical concepts in matrix material which can be seen from the results of student tests on matrix material, it is suspected that this problem is caused by learning models that are less precise and varied to be used in this pandemic period because students tend to learn online and offline, so a learning model is needed in this case. Based on this, experimental research was conducted to determine the differences in students' mathematical concept understanding abilities between classes taught using the flipped classroom model and classes taught using traditional learning models. The selected research subjects were 2 homogeneous classes, with the number of students in the experimental class being 30 people and the number of students in the control class being 30 people. The results showed that the average ability to understand mathematical concepts of students who were taught using the flipped classroom model was 88.3 while students who were taught using the traditional model were 66.07. Based on the results of testing the research hypothesis using the t-test, it can be concluded that the ability to understand students' mathematical concepts in the matrix material of students who are taught using the flipped classroom learning model is more than students who are taught using the traditional (conventional) model.